2012
DOI: 10.1002/lary.23407
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor grilling hazard: Wire bristle esophageal foreign body—a report of six cases

Abstract: Esophageal foreign bodies are frequently encountered, with coin ingestion the most common in the pediatric population and fish bone ingestion the most common in the adult population worldwide. Many people cook with outdoor grills and use wire brushes to clean them. We present the largest case series with six adult cases involving ingestion of wire brush bristles from food prepared on outdoor grilling surfaces. The occurrence of six cases within a small geographic area over a relatively brief time span raises i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…7 Regardless of the retrieval modality, close to 40% of first attempts at removing the bristle have been unsuccessful and close to 22% have required open neck exploration to remove the foreign bodies. 1 Harlor et al 10 and Mortensen et al 1 have suggested the use of contrasted imaging to localize bristles that have migrated, especially those close to vascular structures in the head and neck. We also believe that a contrasted CT with 1–2 mm cuts better highlights anatomy and is more suited for operative planning.…”
Section: Discussionmentioning
confidence: 99%
“…7 Regardless of the retrieval modality, close to 40% of first attempts at removing the bristle have been unsuccessful and close to 22% have required open neck exploration to remove the foreign bodies. 1 Harlor et al 10 and Mortensen et al 1 have suggested the use of contrasted imaging to localize bristles that have migrated, especially those close to vascular structures in the head and neck. We also believe that a contrasted CT with 1–2 mm cuts better highlights anatomy and is more suited for operative planning.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast has been a previously suggested indication for when migration of a foreign body is suspected. 3 In wire bristle ingestion, CT imaging becomes invaluable as a result of its capacity to provide information regarding the size, location, and most important the relationship of the object to important structures as such as the carotid sheath and thyroid gland. Wong et al 1 proposed an algorithm for the management of suspected brush bristle ingestions, beginning with physical examination and flexible fiber-optic laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, treatment for upper aerodigestive tract wire-bristle foreign bodies has ranged from conservative management to surgical exploration, and often multiple procedures are needed before the wire can be identified and removed. 1,3-11 Precise anatomic localization either by radiologic findings or direct visualization is key for safe removal of foreign bodies. This is particularly important when an object is small and becomes embedded deep in the mucosa, as can a wire brush bristle.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of injury ranged from puncture of the soft tissues of the neck to perforation of the gastrointestinal tract; treatment ranged from conservative management to surgical exploration and extraction [1,4]. Most cases pertained to upper aerodigestive tract presentations, with the oropharynx as the most common location [14,8,9]. Far fewer reports have been published on abdominal presentations with injuries past the gastroesophageal sphincter, yet perforation and subsequent need for operative management has been shown to be more prevalent in these types of cases [4,6,7,10].…”
Section: Introductionmentioning
confidence: 99%